The Economic Policy of Muslim Rulers in Iraq and Its Impact on Social Prosperity in The Umayyad and Abbasid Eras - Aahed eabd alkarim muhsin (Peerian Journals Publishing, 2025)
The study aimed to demonstrate the role of economic policy in social prosperity from the early Islamic period until the end of the Abbasid era. It employed several methodologies and discussed zakat and its role in social prosperity، endowments and their role in social prosperity ، trade policy in the early Islamic period، trade policy in the Umayyad era، and in the Abbasid era، agricultural policy in the early Islamic period، the Umayyad era ، and the Abbasid era
Keywords: Policy; The Economic; Impact on Social Prosperity